Vị thế và dự báo xu thế phát triển vùng cửa sông Châu thổ Sông Cửu Long - Dỹ, Nguyễn Địch; Lâm, Doãn Đình; Hà, Vũ Văn; Tấn, Nguyễn Trọng; Tuấn, Đặng Minh; Quảng, Nguyễn Minh (Vietnam Journal of Earth Sciences, 2012)
SUMMARY The position and forecasting the development trend of estuaries area in Cuu Long delta The Mekong delta where Hau river and Tien river, two branches of Mekong river flow in Vietnam by 9 estuaries which include 3 estuaries of Hau river (Tran De, Dinh An, Bat Xac) and 6 estuaries of Tien river (Co Chien, Cung Hau, Ham Luong, Ba Lai, Tien, Dai). Nowadays, Bat Xac estuary has been extended by running process of Hau River from the beginning of 20th century to present; the running process of Ba Lai estuary depends on the regulation of Ba Lai dam. Thus, there are 7 running estuaries in reality. It is noted from the geographical location of estuaries of Mekong delta costal that these estuaries play an important position to physical, economic- social field and defense security as well as international exchanges. To the general trend of the following years, estuary area of Mekong delta coatal will develop powerfully in many fields from economic-social issues to defense security, science and technology, enhancing intellectual standards and life of inhabitant incessantly. It is necessary for administrators to provide policies and effective adaptable solutions with a view to reduce loosing of people and money from breakdowns happened as the global climate changes and the rising of sea water.